Physicochemical and Bacteriological Analysis of Reservoir Water in Ksusta - Yusuf Mungadi Musa; Amina Muhammad; Muzammil Abdulkareem (Biology, Medicine, & Natural Product Chemistry, 2026)
This research work was carried out to determine the bacteriological and physicochemical quality of reservoir water. With the view of evaluating the physicochemical constituent of the reservoir water, we carried out the microbiological analysis of the water sample, and determined the total coliform count of the reservoir water. The physicochemical analysis was carried out using standard methods; the physicochemical analysis revealed that the reserve water samples have slightly acidic to neutral pH, varying conductivity, and acceptable alkalinity and TDS levels. However, the bacteriological analysis indicates the presence of coliform bacteria in all samples, with MPN values exceeding acceptable limits. These findings suggest that the reserve water may pose health risks if consumed without proper treatment. Physicochemical analysis showed pH (6.9-7.1), conductivity (156.1±3.72 - 184.7±9.58 ?S/cm), alkalinity (8.0-8.2), and total dissolved solids (117.1±7.62 - 120.4±2.23 mg/L) within acceptable limits. However, bacteriological analysis revealed the presence of coliform bacteria in all samples, with most probable number values exceeding acceptable limits (21-28). In conclusion, the reserve water’s physicochemical parameters are acceptable, but bacteriological contamination poses health risks. Regular monitoring and treatment are necessary to ensure the water’s safety for consumption.